Aplikasi Konsep Religious Marketing dalam Praktek Komunikasi dan Dakwah Islam - Muhammad Mabrur; Lalu Agus Satriawan; Udi Yuliarto (Fakultas Dakwah dan Ilmu Komunikasi UIN Antasari Banjarmasin, 2024)
The accelerated pace of technological advancement has facilitated the acquisition of information by a multitude of entities. Furthermore, it has altered the behavioural patterns of individuals, enabling the modern person to exercise greater autonomy in determining their own behavioural choices. This development necessitates that da'wah activists adopt innovative approaches to the dissemination of religious teachings. It is not within the power of religious leaders to impose their teachings on society. One such method is the utilisation of marketing concepts in the process of socialising religious teachings, which is commonly referred to as religious marketing. This study was conducted using the library research method with the objective of investigating the potential applications of marketing concepts in the context of da'wah activities. In practice, the marketing mix concept, as applied in commercial marketing activities, can be applied to activities aimed at socialising religious teachings. However, it is important to note that there are several key differences that must be taken into account when implementing the religious marketing concept in the context of promotional activities for religious teachings. One area in which the religious marketing concept is particularly prevalent is in the promotion of zakat funds. It is crucial for zakat fund management institutions to comprehend the tenets of religious marketing, as they must devise innovative strategies to attract donors and encourage them to entrust their zakat funds to these institutions.